Effects of estradiol hormone in menopausal women on anterior disc displacement of temporomandibular joint - Bayu Rosanto Yosaphat; Soetji Rahajoe Poerwati (BIO Web of Conferences, 2020)
Anterior disc displacement is a condition when the articular disc is in the anterior normal position. Epidemiological research shows that the prevalence of TMD is higher in women than in men. Women have a dominant hormone that is not owned by men, the hormone estradiol. Estrogen receptors and the hormone progesterone are found in articular joints in humans. Joint structure, extracellular matrix remodeling, and bone volume modification can be affected by sexual hormones. It was thought to cause changes in connective tissue in the TMJ structure. This study aims to determine the effect of the level of the hormone estradiol in menopausal women on anterior temporal disc displacement of the temporomandibular joint. Subjects were 40 postmenopausal women who were examined for temporomandary joints. The diagnosis of anterior disc displacement was made using the Research Diagnostic Criteria for Temporomandibular Disorders (RDC / TMD) method. Subjects were grouped into subjects with normal tempromandibular joints and subjects with anterior disc displacement. Estradiol hormone was examined by the immunoassay method. This study’s conclusion is estradiol hormone in menopausal women with anterior disc displacement is higher than menopausal women without anterior disc displacement.